Diary of June - Eun-Kung Shin; Ki-beom Jang; Ji-min Kim; Kyung-Soo Im; Cine Wise Film (Firm). ([Pace of production not identified] Cine Wise Film, 2005)
Two boys from the same school are murdered. In their stomachs there are capsules containing scraps from a diary that describe the next victims. Suspecting there might be the possibility that a killer is at the same school, detective Chu Ja-young (Shin Eun-kyung), with her rookie partner Kim Dong-wook (Eric Mun) search the school to find identical handwriting that matches that of the diary excerpts. When they finally find the matching one, they're told that Jin-mo, the student who wrote the text, has died already in a car accident one month previous. As Ja-young and Dong-wook discover Jin-mo's secret diary, more clues are revealed concerning the next victim. They also discover that Jin-mo was bullied by his schoolmates, and that there is a darker secret to be revealed.--https://en.wikipedia.org/wiki/Diary_of_June
Produced by Moo-Rim Byun, Kyung-Soo Im ; music by Taro Iwashiro; cinematography by Cheol-ju Kim.
Eun-Kyung Shin, Ki-beom Jang, Ji-Min Kim, Kkobbi Kim
DVD
In Korean with subtitles in English.
Keywords: Crime; Thriller